2003
DOI: 10.1128/cdli.10.6.1037-1042.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation at the Mitochondrial Large-Subunit rRNA Locus of Pneumocystis Isolates from Simian Immunodeficiency Virus-Infected Rhesus Macaques

Abstract: The nucleotide sequences of a segment of the Pneumocystis mitochondrial large-subunit (mt LSU) rRNA gene from rhesus macaques coinfected with simian immunodeficiency virus (SIV) and Pneumocystis carinii were examined. Of 12 isolates examined, 3 were found to be identical and the others showed substantial sequence variation, with up to 13% divergence among variants. We identified two general sequence types that differed at several sites, including a conserved 26-nucleotide insertion. Four monkeys had evidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Whether the organisms detected in macaques, bats, horses, dogs, ferrets, and other host species represent unique Pneumocystis species remains to be clarified, but these observations support the notion that these organisms are highly ubiquitous and that each mammalian species is infected by at least one Pneumocystis species. Interestingly, based on single-locus PCR studies, wild rats (82), macaques (83,84), bats (85), and dogs (86) are often infected by more than one Pneumocystis population, with sequence divergence approaching or exceeding interspecies levels, raising the question of whether these animals may be infected with more than one distinct species.…”
Section: Species and Taxonomymentioning
confidence: 99%
“…Whether the organisms detected in macaques, bats, horses, dogs, ferrets, and other host species represent unique Pneumocystis species remains to be clarified, but these observations support the notion that these organisms are highly ubiquitous and that each mammalian species is infected by at least one Pneumocystis species. Interestingly, based on single-locus PCR studies, wild rats (82), macaques (83,84), bats (85), and dogs (86) are often infected by more than one Pneumocystis population, with sequence divergence approaching or exceeding interspecies levels, raising the question of whether these animals may be infected with more than one distinct species.…”
Section: Species and Taxonomymentioning
confidence: 99%
“…Excellent rationale exists for use of this model as studies have shown that Pc derived from humans and non-human primates to be phylogenetically most closely related[10, 11]. We performed longitudinal studies to determine association between Pc colonization and progression of airway obstruction and emphysema in the context of an AIDS model.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumocystis cannot be grown in culture. Nevertheless, molecular studies during the last decade have revealed that this genus contains many distinct organisms (Demanche et al, 2001;Denis et al, 2000;Durand-Joly et al, 2000;Guillot et al, 2001;Hunter & Wakefield, 1996;Keely et al, 1994;Ma et al, 2001;Walker et al, 1998;Norris et al, 2003). The genetic and functional diversity exhibited by these organisms suggests that the genus contains more than one species, and three such species have been formally proposed: Pneumocystis jirovecii, the species found in patients suffering from Pneumocystis pneumonia, and Pneumocystis carinii and Pneumocystis wakefieldiae, two species found in laboratory rats (Frenkel, 1976(Frenkel, , 1999Cushion et al, 2004).…”
Section: Introductionmentioning
confidence: 99%